Addressing Biological Invasions in Agriculture with Big Data in an Informatics Age - Rebecca A. Clement; Hyoseok Lee; Nicholas C. Manoukis; Yelena M. Pacheco; Fallon Ross; Mark S. Sisterson; Christopher L. Owen (Agriculture)
Big data approaches are rapidly expanding across many fields of science and are seeing increasing application, yet the use of big data in research related to invasive species lags. Big data can play a key role in predicting, detecting, preventing, controlling, and eradicating biological invasions. Here, we assess terms in the literature related to big data, biological invasions, and agriculture and review sources of big data, including museum records, crowdsourcing observations, natural history collections, and DNA-based information. These sources can be combined with environmental data to build models, predict the origins of invasive species, and develop control methods. To harness the power of data for agricultural biological invasions, several action areas are recommended to streamline processes and improve data sources.